A The Science of Hadith from Ibn Haldun’s Perspective - Ebibi, Faredin; Nuredin, Mensur (International Scientific Journal Vision, 2017)
The general structure of Hadith Science is rich in multiple branches and discipline. One of its major branches is dealing with the treatment of abrogation and what is abrogated. As an abrogation process is permitted in the Islamic Legislation (Shari’ah) and comes in the sense of facilitating and having mercy on believers. It is fact that the Islamic religion takes into consideration the interest and convenience of the believer as a subject who is charged with the transfer and application of divine Message norms. “We do not abrogate any of our arguments or forget it, nor bring it even more useful than it or similar to it. Did you not know that Allah is All-Powerful for all things? “(Qur’an, 2: 106) In the case of confrontation of arguments between denial and affirmation and the inability to compromise or approximate the meaning between them, through interpretation or progress, the last argument is in the role of abrogator. Knowing this discipline is important, meanwhile, it is a serious discipline. In this context, Zuhriu said: “What is the mere prayer of the Islamic jurisprudence (Islam) is the knowledge of the anointing .hadith of the Prophet (sallallaahu alayhi wa sallam)” (En-nuajmi, 2004)